2018
DOI: 10.1007/s00418-018-1710-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of insect-specific RabX6 of Bombyx mori

Abstract: Rab proteins are low-molecular weight (20-25 kDa) monomeric GTPases that are central to the control and regulation of vesicle trafficking. RabX6 is an insect-specific Rab protein that has no close homolog in vertebrates. However, little information about insect-specific Rab proteins is available. In this study, RabX6 was expressed in Escherichia coli and subsequently purified. Antibodies against Bombyx mori RabX6 were produced in rabbits and rats for western immunoblotting and immunohistochemistry. Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Our survey revealed that the set of Rabs of the chordate ancestor was made of at least 41 out of the 42 metazoan Rab subfamilies, of which Rab12 was a chordate gain and RabX6 was a chordate loss occurred before the diversiication of the phylum. Rab12 is strongly expressed in rat Sertoli cells [35] and in migrating neural crest cells [36], and regulates endosomes-lysosomes shift [37]; otherwise, RabX6 is present in neurons and in testis of male insect Bombyx mori [38]. With 41 Rab subfamilies, the current Rab toolkit of the cephalochordate amphioxus may be indeed very similar to the ancestral chordate one, corroborating the 'genomic stasis' attributed to cephalochordates [39][40][41] and supporting the idea that modern amphioxus resembles in many respects the ancestral chordate [42].…”
Section: Rab Evolution In Chordatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey revealed that the set of Rabs of the chordate ancestor was made of at least 41 out of the 42 metazoan Rab subfamilies, of which Rab12 was a chordate gain and RabX6 was a chordate loss occurred before the diversiication of the phylum. Rab12 is strongly expressed in rat Sertoli cells [35] and in migrating neural crest cells [36], and regulates endosomes-lysosomes shift [37]; otherwise, RabX6 is present in neurons and in testis of male insect Bombyx mori [38]. With 41 Rab subfamilies, the current Rab toolkit of the cephalochordate amphioxus may be indeed very similar to the ancestral chordate one, corroborating the 'genomic stasis' attributed to cephalochordates [39][40][41] and supporting the idea that modern amphioxus resembles in many respects the ancestral chordate [42].…”
Section: Rab Evolution In Chordatesmentioning
confidence: 99%
“…The 41 Rab subfamilies of the cephalochordate B. lanceolatum would likely represent the prototypical chordate Rab repertoire that has been preserved in the 'conservative' amphioxus genome. With respect to the metazoan complete toolkit, the ancestral chordate (and thereby, the amphioxus lineage) would have lost a unique gene, the RabX6, which is expressed in neurons and in testis of male insects [38]. The functional causes that may justify the retention of RabX6 in some protostome and non-chordate deuterostome lineages (i.e.…”
Section: The Evolutionary Landscape Of the Rab Gene Family In Chordatesmentioning
confidence: 99%
“…Rab GTPases play pivotal roles in various cellular processes. In terms of reproduction, RabX6, an insect‐specific Rab protein, regulates testicular growth in B. mori (Uno et al ., 2019). For female reproduction, Rab6 is required for membrane trafficking during Drosophila oogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting and immunohistochemistry were done as previously described (Uno et al, 2019). For western blotting, purifi ed proteins (1 μg) were transferred to a PVDF membrane after electrophoresis.…”
Section: Western Blotting and Immunohistochemistrymentioning
confidence: 99%